An AHP enabled port selection multi-source decision support system~and validation: Insights from the ENIRISST project - Dimitrios Georgoulas; Ioannis Koliousis; Stratos Papadimitriou (Journal of Shipping and Trade (JST), 2023)
Analytical Hierarchy Process (AHP) is a robust procedure for ranking options and supporting multi-criteria decision making that determine the port that a shipping operator will select, while designing the most cost-effective route. An important decision that may turn out to be decisive for a company's survival. We developed an AHP based decision support system, as part of a wider Research and data Infrastructure system, that enables practitioners' decision making based on their subjective experience and within realistic time constraints. We test the approach using two regional ports and the throughput results confirmed the initial expectations.
Keywords: 650; AHP; Decision support system; DSS; Greek ports; Port selection